2018
DOI: 10.3390/en11092388
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Frequency Stochastic Optimal Control in Independent Microgrids with Virtual Synchronous Generator-Controlled Energy Storage Systems

Abstract: With the increasing proportion of renewable energy in microgrids (MGs), its stochastic fluctuation of output power has posed challenges to system safety and operation, especially frequency stability. Virtual synchronous generator (VSG) technology, as one effective method, was used to smoothen frequency fluctuation and improve the system's dynamic performance, which can simulate the inertia and damping of the traditional synchronous generator. This study outlines the integration of VSG-controlled energy storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…When a microgrid is islanded, an optimal controller should be designed to minimize the frequency deviations. In recent years, some research works have been reported related to the optimal frequency control issue of an islanded microgrid [7][8][9][10], but most works have focused on proportional-integral-derivative (PID) control method and its different kinds of improved versions based on intelligent optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…When a microgrid is islanded, an optimal controller should be designed to minimize the frequency deviations. In recent years, some research works have been reported related to the optimal frequency control issue of an islanded microgrid [7][8][9][10], but most works have focused on proportional-integral-derivative (PID) control method and its different kinds of improved versions based on intelligent optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, N1 c M,t in Equation (14) denotes the binary parameter for N-1 contingency state of the transmission line between the MV and LV level. The N1 c M,t = 0 forces the transmission flows to be zero when the transmission line is in contingency state and otherwise, N1 c M,t = 1 for normal operations.…”
Section: Objective Function For Outage Operationmentioning
confidence: 99%
“…A smart energy management system to optimize the operation of microgrid was presented by Chen et al [13] where the optimization problem of ESS, economic load dispatch and the optimization of DER was simplified into a single-objective problem. Yang et al [14] proposed a novel stochastic optimal control strategy focusing in independent microgrids based on the integration of ESSs and traditional synchronous generators. The approach was based on an improved design of linear quadratic Gaussian controller and the consideration of the ESS's current state of charge (SOC) that prevented the batteries' overcharging and overdischarging problems, thus adaptively regulating the power output to minimize the frequency fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing the rotor swing equation, the virtual inertia and primary frequency regulation instructions were conceived to simulate the external characteristics of the SG using this concept. The VSG can increase the inertia of the inverter and improve the system output response [6][7][8][9]. Although the VSG is equivalent to the traditional synchronous generator in terms of output characteristics, it is still difficult to maintain system stability under high transient conditions.…”
Section: Introductionmentioning
confidence: 99%